Development of the mosquito pathogen Leptolegnia chapmanii (Straminipila: Peronosporomycetes) on an inexpensive culture medium based on sunflower seed - Rueda Páramo, Manuel Enrique (2015)
An inexpensive culture medium based on sunflower seed extract (SSE) for production of L. chapmanii was developed. Vegetative growth on solid and liquid SSE was compared with two culture media used routinely (PYG and Emerson YPss). Results indicate that the oomycete is able to grow on SSE medium, producing more zoospores at a faster rate as well as inducing higher mortality rates in Ae. aegypti larvae.